Fables. [21], Happily ever after - Willingham, Bill (DC Comics/Vertigo, 2015)
"In the aftermath of Bigby Wolf's destruction, a shift in the Fables' underlying power structure threatens to split the community into two warring factions - one led by Snow White, the other led by her sister Rose Red."